2018
DOI: 10.1016/j.celrep.2018.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthesis and Metabolite Overflow Contribute to Energy Balancing in Cyanobacteria

Abstract: Understanding how living cells manage high-energy metabolites such as ATP and NADPH is essential for understanding energy transformations in the biosphere. Using light as the energy input, we find that energy charge (ratio of ATP over ADP+ATP) in the cyanobacterium Synechocystis sp. PCC 6803 varies in different growth stages, with a peak upon entry into the rapid growth phase, as well as a positive correlation with light intensity. In contrast, a mutant that can no longer synthesize the main carbon storage com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 30 publications
5
89
0
Order By: Relevance
“…However, from the perspective of optimal resource allocation, glycogen accumulation is seemingly suboptimal, since the required energy and carbon is stored and not utilized to enhance growth. Various growth limitations are known to induce accumulation of storage products, including glycogen (Monshupanee and Incharoensakdi, 2014), and a recent study showed that glycogen plays an important role in energy balancing and energy homeostasis in Synechocystis (Cano et al, 2018). We therefore hypothesize that the observed increase in glycogen content, in the absence of other stress factors, is consistent with a limitation in standard BG-11 medium.…”
Section: Maximal Growth Rates and Glycogen Accumulationsupporting
confidence: 55%
“…However, from the perspective of optimal resource allocation, glycogen accumulation is seemingly suboptimal, since the required energy and carbon is stored and not utilized to enhance growth. Various growth limitations are known to induce accumulation of storage products, including glycogen (Monshupanee and Incharoensakdi, 2014), and a recent study showed that glycogen plays an important role in energy balancing and energy homeostasis in Synechocystis (Cano et al, 2018). We therefore hypothesize that the observed increase in glycogen content, in the absence of other stress factors, is consistent with a limitation in standard BG-11 medium.…”
Section: Maximal Growth Rates and Glycogen Accumulationsupporting
confidence: 55%
“…Glycogen synthase genes, absent in plastids, were possibly among the first genes to be lost and this event may have helped to achieve the early hostÀendosymbiont metabolic integration (Gavelis & Gile, 2018). Glycogen synthase-defective mutant cyanobacteria release organic carbon outside the cell as a homeostatic response to cope with excessive photosynthate production and the inability to store it as glycogen (Cano et al, 2018). Therefore, it is possible that inefficient glycogen storage allowed the leakage of photosynthates that could be used by the host before the evolution of a specific and more efficient photosynthate export system.…”
Section: Arc Ha Ep La S T Id Amentioning
confidence: 99%
“…(Cano et al, 2018), there might even be a flux of 12 C to 1,2-propanediol via the glycogen pool, which would not be seen in our experiments. Due to the glycogen synthesis and degradation cycle, which maintains the energy balance in Synechocystis sp.…”
Section: 2-propanediol Is Partly Derived From Glycogenmentioning
confidence: 54%
“…Due to the glycogen synthesis and degradation cycle, which maintains the energy balance in Synechocystis sp. (Cano et al, 2018), there might even be a flux of 12 C to 1,2-propanediol via the glycogen pool, which would not be seen in our experiments.…”
Section: Minimizing 13 Co 2 Consumption For Costefficient Labeling mentioning
confidence: 54%